Synergistic effect of sunflower oil and soybean oil as alternative processing oil in the development of greener tyre tread compound - Mohamed, N R; Othman, N; Shuib, R K (Journal of Rubber Research, 25(#): 239-249., 2022)
Bio-based oil is an evolving oil with the potential to replace mineral oil from petroleum as a plasticiser in elastomers. Mineral oil has been described as environmentally harmful and derived from a non-renewable resource. Hence, this study investigates the potential of sunflower oil and soybean oil as bio-based processing oils in producing greener tyre treads. The ternary rubber blends with alternative processing oil (sunflower oil and soybean oil) were compared to a standard rubber vulcanizate containing petroleum-based mineral oil. Resultantly, the cure time and rheometric torque of bio-based oils were equivalent to mineral oil. However, a modest increase in the scorching time indicated that both bio-based oil compounds offer better processing safety and have lower crosslinking density than mineral oil. The sunflower oil compound reflected better tensile strength and abrasion resistance compared to the standard rubber vulcanizate with increments of up to 20.42 MPa and 227, respectively. Meanwhile, soybean oil significantly increased in tear strength up to 98.36 N/mm and offered a good fuel efficiency. Mineral oil compounds revealed a comparable dynamic mechanical performance in the elastic response under dynamic deformation and skid resistance compared to bio-based oil compounds.
Keywords: Ternary rubber blends; Tyre tread; Bio-based oil; Sunflower oil; Soybean oil; Dynamic mechanical analysis (DMA)